Kegiatan Pengabdian Masyarakat Dengan Pemeriksaan Liang Telinga dan Gendang Telinga Dalam Rangka Menjaga Kesehatan Telinga pada Kelompok Usia Remaja di SMA Kalam Kudus 2 - Yohanes Firmansyah; Alexander Halim Santoso; Vincent Aditya Budi Hartono; Clarissa Hartawan; Edwin Destra; Farell Christian Gunaidi (Jurnal Informasi Pengabdian Masyarakat, 2024)
Ear health is a combination of maintaining the structural and functional integrity of the ear to ensure optimal auditory function. This community service activity aimed to enhance adolescents' understanding of the importance of ear canal and tympanic membrane examinations in preserving ear health. The methods employed in this activity included education and ear examinations using the Plan-Do-Check-Act (PDCA) approach. The educational sessions covered topics such as risk factors, proper ear hygiene, and the significance of early detection of ear disorders. Examinations were conducted to assess the condition of the ear canal and tympanic membrane among participants. The results demonstrated an improvement in participants' understanding of ear health maintenance and a reduction in risky behaviors, such as the use of foreign objects in the ear. This community service initiative highlights the importance of ear health preservation through healthy habits and regular examinations to prevent hearing impairment. Therefore, educational and examination activities can help adolescents adopt practices that support auditory health and raise awareness about the significance of preventive measures.: